From "what is new political economy" to "why is everything new political economy?" - Rafael Galv\~ao de Almeida (Duke University, Center for the History of Political Economy (CHOPE), 2018)
In this paper I aim to try defining New Political Economy (NEP) as the economic study of politics, with a macroeconomic focus. It emerged from the influences mainly from the criticism of theory of economic policy, political business cycle research, public choice theory and new institutional economics. Due to its ample nature, different economists have different understandings of what it is, and their definitions may clash against each other. This article aims to be a contribution to dissipate this confusion.
Keywords: B22; B25; D7; 330; political economy; new political economy; public choice; new institutional economics; political economics; political macroeconomics; theory of economic policy; political business cycles; economics and politics; positive political economy